2009
DOI: 10.1002/micr.20614
|View full text |Cite
|
Sign up to set email alerts
|

Vein grafting in fingertip replantations

Abstract: In this retrospective study, the survival rates of fingertip replantation with and without vein grafting were evaluated along with their postoperative functional and cosmetic results. One hundred twenty-one-fingertip amputations were performed in 103 patients between September 2002 and July 2007. Thirty-four amputated fingertips were replanted without vein grafting, while 87 amputated fingertips were replanted with vein grafting for arterial and/or venous repairs. The overall survival rates of the replantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The absence of relationship between grafts and poor outcomes was maintained when subgroup analysis was performed on arterial versus venous complications. Other authors have demonstrated similar findings, with no effect of vein grafts on survival of digital replantation (Yan et al, ). High‐level evidence based on studies on the use of anticoagulation in finger replants with vascular grafts are lacking, but many advocate that some form of anticoagulation with heparin may be beneficial.…”
Section: Discussionsupporting
confidence: 62%
“…The absence of relationship between grafts and poor outcomes was maintained when subgroup analysis was performed on arterial versus venous complications. Other authors have demonstrated similar findings, with no effect of vein grafts on survival of digital replantation (Yan et al, ). High‐level evidence based on studies on the use of anticoagulation in finger replants with vascular grafts are lacking, but many advocate that some form of anticoagulation with heparin may be beneficial.…”
Section: Discussionsupporting
confidence: 62%
“…Twelve studies included only cases in which a specific operative technique (vein graft, artery only, delayed venous repair etc.) was used 17, 20, 26, 28–30, 32, 34, 3638, 40 . Five studies did not present the number of patients studied 11, 14, 18, 24, 25 , 6 studies did not present data about which digit was amputated 11, 18, 19, 24, 32, 37 , and 9 studies made no mention of the nature of injury that led to the amputation 11, 16, 18, 2426, 30, 32, 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was similar to the "pre-osteosynthesis vein graft technique" described by Ikeda et al 9 in 1994, but skeletal fixation was not applied in most cases, consistent with Sabapathy et al 10 The vein graft was long enough to reach the proximal phalanx, which is much longer than previously reported. 7,9 This long vein graft could usually be harvested from the dorsum of the foot, where the subcutaneous veins have various branches with sizable diameters that are adequate for grafting. The anastomosis between the artery in the amputated fingertip and the vein graft was first performed on the back table where the amputated fingertip and vein graft could be placed under a microscope and held in the optimal positions for anastomosis (►Fig.…”
Section: Operative Proceduresmentioning
confidence: 99%